Strategi Komunikasi Penganut Agama Baha’i dalam Membangun Citra Positif di Masyarakat - Illi Apriliyadi (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2020)
Negative images are often experienced by co culture groups in the community, as experienced by Baha’i religious followers. Therefore they need a communication strategy in building a positive image in the community. This study aims to determine the communication strategies of Baha'i followers in the village of Cebolek Kidul, Margoyoso sub-district, Pati regency in building a positive image in the community. This study examines the components of communication strategies in terms of message planning, communication approaches, and media selection. This research uses the co-culture theory by Mark Orbe. The interpretative phenomenological analysis used in this study as analytical techniques of the data. The Result of this study show that Baha’i followers uses an Accommodation strategy to build a positive image in the community. This strategy ranges on the Non-Assertive Accommodation and the Assertive Accommodation. In the aspect of planning the message, the Baha'i Pati held a meeting with members of the local spiritual assembly before the message is delivered to the community. The communication approach is carried out by way of friendship with residents and local government officials, using verbal and non-verbal language by showing smiles and polite language. Finally in the aspect of media selection, Baha'is in the village of Cebolek use brochures and film screenings on Baha'is, this is done so that the public understands and knows about the teachings of the Baha’i faiths.